Desafios para a inserção social dos catadores de materiais recicláveis e reutilizáveis na coleta seletiva em Simão Dias/SE - Oliveira, Ariane Siqueira de (2019)
The problem that involves the inadequate management of household solid waste has been common in Brazilian municipalities, especially in small ones. Selective collection, when well structured, is capable of minimizing socio-environmental impacts, since it adds market value to solid waste and promotes the social insertion of recyclable and reusable material collectors. The research aims to analyze the challenges for the social insertion of recyclable and reusable material collectors in the selective collection in the city of Simão Dias/SE. The method used was Hypothetical-Deductive with a qualitative-quantitative approach. Data collection was divided into two phases: theoretical exploration through documentary and bibliographic review and field research using field diary, in situ observation, photographic records and semi-structured interviews, with a public official 40 collectors, a representative of the cooperative, a local Content analysis was used to systematize and analyze information. The selective collection in the city of Simão Dias is configured through formal and informal scavengers. The former operate through the Simão Dias Recyclers' Collectors and Recyclers Cooperative (COOCAMAR), collecting materials on public roads, homes and commerce. These workers collect and forward the materials to the cooperative shed where they carry out sorting, weighing, pressing and marketing. This group works in partnership with the City Hall, through a service agreement. Already the informal scavengers work autonomously collecting on public roads and in the garbage dump. The research reveals that the pickers who work in the selective collection of Simão Dias are mostly: men, brown, with low schooling, age between 30 and 49 years old, who own their own residence and earn less than a minimum monthly salary. The formalization of collectors aims to organize work democratically through collective engagement, empowerment of those involved and self-management of the cooperative in an emancipatory and equitable perspective. It was identified that if there was a greater social participation, the collection of material would increase and consequently the gains among the members. The challenges faced by the cooperative are related to the lack of assiduity, punctuality, integration among the cooperative, the lack of adequate and proper place, lack of selection and screening of the materials beyond the need to publicize the work. Selective collection is of singular relevance for the efficient and effective management of solid waste. In this sense, it is fundamental to develop environmental education projects to sensitize and promote the participation of public power and the community, in order to meet the aspirations of the collectors, promote their social insertion and the sustainability of the cooperative.